Обряд на падающую звезду: [роман] / Татьяна Форш - Форш Татьяна Алексеевна (Знаки судьбы, 2016)
Экземпляры: ф.16 (20170920) / Инвентарный номер: 57584 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ф 80 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44